G-protein Coupled Receptor Signaling in Pluripotent Stem Cell-derived Cardiovascular Cells: Implications for Disease Modeling - Dolatshad, Nazanin F.; Hellen, Nicola; Jabbour, Richard J.; Harding, Sian E.; Földes, Gabor (Frontiers in Cell and Developmental Biology, 2015)
Human pluripotent stem cell derivatives show promise as an in vitro platform to study a range of human cardiovascular diseases. A better understanding of the biology of stem cells and their cardiovascular derivatives will help to understand the strengths and limitations of this new model system. G-protein coupled receptors (GPCRs) are key regulators of stem cell maintenance and differentiation and have an important role in cardiovascular cell signalling. In this review, we will therefore describe the state of knowledge concerning the regulatory role of GPCRs in both the generation and function of pluripotent stem cell derived-cardiomyocytes, -endothelial and -vascular smooth muscle cells. We will consider how far the in vitro disease models recapitulate authentic GPCR signalling and provide a useful basis for discovery of disease mechanisms or design of therapeutic strategies.